2019
DOI: 10.1016/j.heliyon.2019.e01155
|View full text |Cite
|
Sign up to set email alerts
|

A theoretical analysis of elastic and optical properties of half Heusler MCoSb (M=Ti, Zr and Hf)

Abstract: Ab initio calculation of the Elastic and Optical properties of cubic half-Heusler compounds MCoSb (M = Ti, Zr and Hf) are reported using the FP-LAPW approach of the Density Functional Theory. Generalized Gradient Approximation was used as the exchange and correlation potential for investigating these properties. It was found that the Bulk modulus decreases with the increase in temperature and increases with the increase in pressure for all of the three Heusler compounds under study. The Debye's temperature alo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(17 citation statements)
references
References 29 publications
(39 reference statements)
3
14
0
Order By: Relevance
“…Therefore, BaAgP is a better candidate for photovoltaic material. The static refractive index, n(0) satisfies the relation n(0) 2 ≈ ε1(0), which verifies the accuracy of the calculation[68]. It is observed from the Fig.6(c) that beyond n(0), refractive index starts to increase up to ~2.10 eV and reaches a maximum value of 4.33 along a-axis and along c-axis this value is 3.70 at ~2.62 eV.…”
supporting
confidence: 71%
See 3 more Smart Citations
“…Therefore, BaAgP is a better candidate for photovoltaic material. The static refractive index, n(0) satisfies the relation n(0) 2 ≈ ε1(0), which verifies the accuracy of the calculation[68]. It is observed from the Fig.6(c) that beyond n(0), refractive index starts to increase up to ~2.10 eV and reaches a maximum value of 4.33 along a-axis and along c-axis this value is 3.70 at ~2.62 eV.…”
supporting
confidence: 71%
“…Fig.6(d)shows the photon energy (frequency) dependent extinction coefficient for BaAgP. It is observed that the trends of k(ω) is similar to that of ε2(ω) because it also provides a measure of absorption of incident radiation[68]. The maxima of extinction coefficient occurs at about 2.63 eV along a-axis and 3.18 eV along c-axis.…”
mentioning
confidence: 78%
See 2 more Smart Citations
“…All other optical constants follow from the dielectric functions using standard equations. 29,39 The intraband transition contribution to the dielectric functions are inconspicuous, given the semiconducting nature of the compounds, and also the indirect interband transitions are neglected with comparison to direct interband transition, considering low photon momentum. The plot of the real part of the dielectric function with respect to the incident photon energy, at 0 and 10 GPa pressure, is shown in Figure 6 The optical conductivity plots shown in Figure 7(a)−(c) show a forbidden conduction region with energies corresponding to higher infrared and lower visible spectra, which further reconfirms the semiconducting nature of the compound.…”
mentioning
confidence: 99%